2019
DOI: 10.17159/sajs.2019/5271
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and motivation in sport: The mediating role of mental toughness

Abstract: An extensive body of research has been done on the links between perfectionism and motivation, yet the underlying mechanisms linking these psychological characteristics have been underexplored. In this study, we used an integrative modelling approach to examine associations between dimensions of perfectionism (i.e. personal standards [PSP] and concerns over mistakes [CMP]), mental toughness (MT) and motivational orientations (i.e. self-determined motivation [SDM] and non-self-determined motivation [NSDM]). Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
1
9
0
3
Order By: Relevance
“…The key moments of victory were related, in particular, to the achievement of the set goal (as shown by the scale of implementation of mental resistance tasks. As reported by Cowden et al, high mental resilience promotes higher perfectionism (as revealed by the study), higher motivation, and setting optimal goals [84]. The UM runner was motivated by his training staff.…”
Section: Motivational and Psychological Factorssupporting
confidence: 70%
“…The key moments of victory were related, in particular, to the achievement of the set goal (as shown by the scale of implementation of mental resistance tasks. As reported by Cowden et al, high mental resilience promotes higher perfectionism (as revealed by the study), higher motivation, and setting optimal goals [84]. The UM runner was motivated by his training staff.…”
Section: Motivational and Psychological Factorssupporting
confidence: 70%
“…In this sense, it seems necessary to train these constructs. However, although MT is improved by training (Dohme, Bloom, Piggott & Backhouse, ), it must be kept in mind that MT has shown a relationship with aspects of personality that are innate, such as perfectionism (Cowden, Crust, Jackman & Duckett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Perfectionism is characterized as a multidimensional trait related to the individual's desire to achieve a high standard of performance accompanied by a critical tendency towards their performance (Cowden et al, 2019;Stoeber, 2018). Scientific evidence separates two great dimensions of perfectionism, an adaptive and other that is less adaptive (Cowden et al, 2019;Hill & Madigan, 2017;Stoeber, 2018).…”
Section: Introductionmentioning
confidence: 99%